Experimental Evidence on the Benefits of Eliminating Exchange Rate Uncertainties and Why Expected Utility Theory causes Economists to Miss Them - Jürgen von Hagen; Sebastian Kube; Reinhard Selten; Robin Pope (University of Bonn, Bonn Graduate School of Economics (BGSE), 2006)
Conclusions favorable to flexible exchange rates typically accord with expected utility theory in ignoring the costs that exchange rate uncertainty generates for governments, central banks, firms and unions in: (i) choosing among acts; and (ii) existing until learning the outcome of the chosen act. Allowing for these involves SKAT, the Stages of Knowledge Ahead Theory, Pope (1983, 1995, 2005), Pope, Leitner and Leopold (2006). A laboratory experiment suggests that (i) and (ii) together outweigh the advantages of having a flexible exchange rate as an additional instrument for managing a country?s international competitiveness goal.
Keywords: F33; D80; D81; F31; 330; exchange rate regime; exchange rate uncertainties; currency union; macro-economic instruments; experiment; SKAT